Selenomethionine Supplementation Contributes to Reducing Oxidative Stress and Inflammation Markers following Exercise-Induced Muscle Damage - Roy Januardi Irawan; Heri Wahyudi; Nanda Rimawati; Adi Wijayanto (OVS LLC, 2024)
Background. Exercise-induced muscle damage (EIMD) is a temporary response to intense or prolonged exercise that can cause muscle pain, inflammation, and impaired muscle function. Antioxidant supplementation is a proposed strategy to reduce EIMD symptoms by targeting reactive oxygen and nitrogen species (RONS) involved in the process. Objective. The study aimed to investigate the effect of Selenomethionine supplementation on malondialdehyde (MDA) and C-reactive protein (CRP) levels resulting from Exercise-Induced Muscle Damage (EIMD). Materials and methods. This study used a randomized pretest-posttest control group design, involving a total of 32 male recreational students from the State University of Surabaya (Indonesian: Universitas Negeri Surabaya), (age 19.25 ± 0.76 years, body mass 63.16 ± 3.38 kg, height 167.28 ± 4.54 cm, body fat 19.60% ± 4.57%). The participants were randomly assigned to the selenomethionine group (SEM, 100 µg/day) or placebo group (PLA, corn starch 100 mg/day) for a period of 28 days (4 weeks). On days 1 (baseline) and 29, participants underwent a single bout of EIMD. Blood samples were collected 24 hours post-EIMD to measure MDA and CRP concentrations in plasma. The statistical analysis was conducted using paired sample t-test. Results. The placebo group experienced a significant increase in plasma MDA and CRP concentrations after EIMD compared with baseline values (p < 0.05). However, the SeMet group showed lower plasma MDA and CRP levels than the placebo group. Conclusions. Daily Selenomethionine supplementation for 28 days has been found to reduce oxidative stress by lowering MDA levels in the blood and to decrease inflammation by reducing CRP levels post-exercise-induced muscle damage. This indicates a lower risk of EIMD due to reduced oxidative stress and inflammation.